The Influence of Jerojer Artists' Modalities in "Cerbera" on Market Segmentation - Coffea Ina Wa Yaskurun; Ghaitsa Zhahira Shafa; Syahria Millatus Salma LHB; Gloria Christine Lembong Purwanto (Journal of Interdisciplinary Social Sciences and Humanities, 2025)
Jerojerrr is an artist whose works are all modeled after drawings, made with shading techniques using graphite on canvas media. One of his works entitled "Cerbera" is one of 5 works in his series entitled "Half Past You", created in 2023, this series consists of 5 works namely "Flight of the Yellow Jacket", "Perpetuity", "Pavane For a Dead Princess", "Cerbera", and "Liebestraum". All the works in this series were created using the shading technique on canvas and were exhibited and sold at the exhibition titled "MASQUERADE" on November 10-12, 2023 held at the Unicorn Young Collectors Club (UYCC) Art Gallery. "Cerbera" is one of the works from Jerojerr's "Half Past You" series that sold quickly at that time, therefore this research will discuss how much Pierre Bourdieu's theory of modality influences Jerojerr's work entitled Cerbera so that it is able to attract interest from certain market segments, influence commercial decisions in the art world, and the sale of the work.